Molecular insights indicate that Pachycara thermophilum (Geistdoerfer, 1994) and P. saldanhai (Biscoito and Almeida, 2004) (Perciformes: Zoarcidae) from the Mid-Atlantic Ridge are synonyms species - Stefanni, S. (2007)
The genus Pachycara comprises of 20 species distributed across the globe. Due to difficulties in collecting these fish, most of the species were described from single or few individuals. Until now, the systematics for these species has been based on traditional taxonomy and the only studies with molecular interest were performed on the Circum Antarctic Pachycara brachycephalum.